Inefficient Lobbying, Populism and Oligarchy - Campante, Filipe R.; Ferreira, Francisco H.G. (World Bank, Washington, D.C., 2013)
The authors investigate the theoretical effects of lobbying and pressure group activities on both economic efficiency and on equity. Looking at lobbying as a political activity that takes place alongside production, they find that lobbies may generate economic inefficiency as part of the process of shifting the allocation of government expenditures in their favor. Outcomes of this non-electoral political process will always be biased toward the group with a comparative advantage in politics, rather than in production. In a context where the main political conflict is one between "the rich" and "the poor," political equilibria may be either populist (inefficiently pro-poor) or oligarchic (inefficiently pro-rich), depending on each group's lobbying effectiveness.